The social-cognitive mechanisms regulating adolescents' use of doping substances - Lucidi, F.; Zelli, A.; Mallia, L.; Grano, C.; Russo, P. M.; Violani, C. (Journal of Sports Sciences, 2008)
In this study, we assessed the longitudinal effects of social-cognitive mechanisms on the self-reported use of doping substances and supplements among Italian high school students. In total, 1232 students completed questionnaires measuring various psychological factors hypothesized to influence students' intention to use substances. Three months later, 762 of the students completed the same questionnaires a second time and also reported their use of substances during the time between assessments. Overall, the percentages of students using doping substances (2.1%) or supplements (14.4%) were consistent with values reported in the literature. Analysis of the data showed that adolescents' intention to use doping substances increased with stronger attitudes about doping, stronger beliefs that significant others would approve of their use, a stronger conviction that doping use can be justified, and a lowered capacity to resist situational pressure or personal desires. In turn, stronger intentions and moral disengagement contributed to a greater use of doping substances during the previous 3 months. Doping use was also correlated significantly to supplementation. In conclusion, our results provide novel information about some of the psychological processes possibly regulating adolescents' use of doping substances and supplements. The results also highlight possible areas for future study and intervention, focusing on the prevention of adolescents' substance use.